2020
DOI: 10.1038/s42003-020-1013-2
|View full text |Cite
|
Sign up to set email alerts
|

An automated platform to monitor long-term behavior and healthspan in Caenorhabditis elegans under precise environmental control

Abstract: Health and longevity in all organisms are strongly influenced by the environment. To fully understand how environmental factors interact with genetic and stochastic factors to modulate the aging process, it is crucial to precisely control environmental conditions for long-term studies. In the commonly used model organism Caenorhabditis elegans, existing assays for healthspan and lifespan have inherent limitations, making it difficult to perform large-scale longitudinal aging studies under precise environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…Thus, it is possibly reducing attrition rates for the downstream phases of the drug development process. We also observed that various behavioral features declined during the aging process, as like other model organisms 11,40 . This observation points that our platform and pipeline can establish the areas in which Daphnia can complement existing models through improvements in sensitivity, cost, or efficiency for the aging research and phenotypic screening for the anti-aging drug discovery.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, it is possibly reducing attrition rates for the downstream phases of the drug development process. We also observed that various behavioral features declined during the aging process, as like other model organisms 11,40 . This observation points that our platform and pipeline can establish the areas in which Daphnia can complement existing models through improvements in sensitivity, cost, or efficiency for the aging research and phenotypic screening for the anti-aging drug discovery.…”
Section: Discussionsupporting
confidence: 74%
“…Next we tested how well the model can be used to track motion in a realistic biological discovery context: examining behavioral decline in the aging process. Behavior and movement are common methods to gauge the health and physiological age of an individual (Golden et al 2008; Hahm et al 2015; Zhang et al 2016; Churgin et al 2017; Le et al 2020). For these experiments, it can be challenging to accurately measure how the movement of individuals changes throughout their entire lifespan due to complex environmental conditions and the large-scale of the data.…”
Section: Resultsmentioning
confidence: 99%
“…See prior work for more details. (Le et al 2020) Training Faster R-CNN network For the egg detection and aging model, we used TensorFlow GPU (v 1.14) to train the model. For the developmental tracking model, we used TensorFlow CPU (v 1.14).…”
Section: Elegans On-chip Culturementioning
confidence: 99%
“…In conclusion, we here present a tool that is capable of predicting C. elegans healthspan, based on myofilament features, as exemplified by our analysis of an insulin/IGF1-like signaling mutant. In its current form, this tool can be used downstream of the many high-throughput screens for genes, treatments and compounds that modulate healthspan in C. elegans (Bulterijs and Braeckman, 2020; Le et al, 2020; Luyten et al, 2016; Sayed et al, 2021). It objectively probes for the effect of such treatments on sarcopenia, an age-related pathology conserved from worms to humans.…”
Section: Discussionmentioning
confidence: 99%